The effect of a radial magnetic field on thermal convection in a rotating cylindrical annulus - REVALLO, Miloš (Contributions to Geophysics and Geodesy, 2008)
The problem of rotating magnetoconvection in a cylindrical annulus in the presence of a radial magnetic field is considered. Previous studies show that convective instability has the form of waves travelling in azimuthal direction. Due to the applied magnetic field the dispersion curve for the Rayleigh number possesses two local minima. Here we explore this feature in dependence on the system parameters. We also find conditions for the two local minima existence.